Implications of the new european union nonfinancial reporting directive - Harjula, Tomi Santeri (2015)
The European Union introduced a new directive on non-financial reporting, which should be implemented into member state legislation in 2016 and effective in business year 2017. This paper introduces the legislation and some implications it will have. Also there will be discussion of the general trends on sustainability and corporate social responsibility, and how those are related to the EU directive. The research question for this paper is “what are the implications of the EU directive on nonfinancial reporting?” The question is approached on academic level with discussion of the broader topics around the matter and also on research level with analysis of several questionnaires on non-financial reporting. In the analysis it was found that non-financial reporting is really a global standard now and companies should no longer ask if they should report but rather how to report and what information to include in those reports. Also majority of investors are now expecting transparent and coherent reports on non-financial performance and companies should address this with careful consideration. On the other hand, it was found out that current reporting standards are not sufficient enough and there will be a lot of work to do to reach a sufficient level of quality. Furthermore, the directive is compromising and does not provide a framework to reach the eligible level of quality. Hence the directive mostly serves as a strong statement by the European Commission to support sustainable development and brings hope of positive future development. Even more, the directive does not solve any current problems in the field of sustainability and there is a lot of work to do in international context to address the complex problems of modern society.